Design and Construction of a Web-Based Employee Salary Calculation System for the Manokwari Regency Cryptography, Communication and Informatics Service - Yopi Giban; Sofyan Sofyan; Joice Pangulimang; Yuliana Sangka (Pt. Anagata Sembagi Education, 2025)
The development of information technology provides a significant opportunity for government agencies to improve the efficiency and effectiveness of administrative services, including in the management of employee salaries. The Manokwari Regency Code, Communication and Informatics Office still uses a manual system in the process of calculating and recording employee salaries, which is prone to errors, delays, and a lack of transparency. Therefore, this study aims to design and build a web-based employee salary calculation system that can help the salary data processing process to be more accurate, fast, and easily accessible. The method used in designing this system is the waterfall software development method, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. This system is designed using a web-based programming language with an integrated database to store employee data, salary components, and deductions such as bank credit, social gatherings, and other contributions. The result of this study is a salary calculation information system application that can be accessed via a local network or the internet, with automatic calculation features, payslip printing, and employee salary history.